Determinantes da diversidade alfa da assembleia de peixes da região litorânea de lagoas de inundação. - Lopes, Taise Miranda (2013)
Ecological niche can be described as a range of environmental features that particular species requires to achieve a positive population growth. The theory of ecological niche is based on the determination of how groups of species are distributed in nature, and the influence of environmental variables, as well as the biological interactions. The environmental variables are a major factor structuring communities, spatially and temporally. We tested the hypothesis that the fish community in the littoral region of floodplain lakes of the upper Paraná River is related to environmental variables, which reflect the physical structure of the habitats, water features (physicochemical variables) and productivity. To determine the main determinants of diversity alfa of fish assemblage, a total of 16 environs belonging to the rivers Baia, Ivinhema and Paraná were sampled. Samples were collected quarterly from March to December 2010, and the environmental variables measured were: area, depth and macrophytes species richness (structural habitat variables); temperature, dissolved oxygen, pH, conductivity and water transparency - Secchi depth (physic-chemical variables); chlorophyll-a, total nitrogen, total phosphorus and total suspended solids (variables of productivity). Fish were collected with seining nets in the littoral region of the lakes. Fish species richness was lower in March and higher in September and evenness presented an inverse trend. For species richness, ANOVA was significant for the factor month, and March was different from the other months. Evenness did not differ among the considered factors. The patterns of similarity in the composition of the fish assemblage were summarized by NMDS. The PERMANOVA identified significant differences in the composition of fish species among the factors month and system, and their interaction, indicating that the trend in the months depended the system considered. To determine the environmental variables related to diversity alfa, a multiple regression was conducted, using the scores of PCA axes retained for interpretation as explanatory variables, and diversity alfa as response variable (axis 2 of the PCA was significant to the model). Environmental variables most related to axis 2 of the PCA were depth, temperature and dissolved oxygen. Thus, diversity alfa was influenced by the increased depth of the floodplain lakes in March, which led to an increase in the amount of organic matter in the water column (quickly decomposed due to high temperatures) and, consequently, to a decrease in the concentrations of oxygen. Thus, the combination of these three variables was the main determinants of the diversity alfa of the fish assemblage of the littoral region of these floodplain lakes.